RESPON MASYARAKAT TERHADAP KEBERADAAN PASAR KAGET DI KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU Studi pada Pasar Kaget Riau Indah Lestari Kelurahan Tuah Karya Kecamatan Tampan Kota Pekanbaru Tahun 2014 - Fajar Alan Syahrier; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Research on Community Response Against Shocked the Market Presence in the Village District of Tampan Tuah Karya Pekanbaru (Studies in Riau Indah Lestari Shocked the Market Village District of Tampan Tuah Karya Pekanbaru 2014). This study was conducted in one of the markets that are in the Village shocked Tuah Karya which operates from 7:00 to 12:00 PM. The formulation of the problem in this study are How Community Response and Public Expectations RT 05 RW 06 Sub Tuah Karya Against shock market presence in the Village Tuah Karya shocked Riau Indah Lestari particular market? In this study, the author uses descriptive quantitative method, which is done by obtaining and analyzing the data is numeric. This method as a process of solving a problem that is studied by describing the state of an object of research based on the facts available. o obtain the data necessary to make observations at the site author Shocked the Market research and public Riau Indah Lestari RT 05 RW 06 Sub Tuah Karya District of Tampan, Pekanbaru and conduct interviews with relevant parties, namely the Department of Market. The results showed that the presence of market shock is very helpful around the housing society, although this distance shocked the market with the official traditional market is not too much pulling people prefer to shop at this market. Market presence shocked not only facilitate residents to shop around for day-to-day or weekly, but the price of the goods sold are relatively cheaper, so that people find it easier and cheaper in the shop. However, the presence of market shock also have negative effects on the environment and public order, such as causing congestion, market stalls and looks shabby for trash scattered about, and cause odor. Public expectations for this market very well, they expect the market shock well organized and neat and worthy to be used as the official market. To that end, the Government through the Department of Market Pekanbaru City should make regulations aimed at controlling the market Shocked so cleanly and beneficial to all. Keywords: Community Response, Hope Society, Markets Shock